Effect of Temperature Semi-solid Casting Process on AZ91D Magnesium Alloys to Hardness and Microstructures - Kusharjanto Kusharjanto; Sutarno Sutarno; R. Henny Mulyani (Indonesian Journal of Physics, 2019)
This study investigates the effect of temperature semi-solid casting process for magnesium alloys AZ91D in an effort to increase the mechanical properties for the application of lightweight structures. In this experiments, semi-solid casting process is varied temperatures ranging from 500, 510, 520, 530 and 540°C. Results of hardness testing obtained the highest average is 64.4 BHN at a temperature of 500°C, which higher than the as-cast 42.56 BHN (an increase of 33.91%). The increasing of hardness occur because of changes in the microstructure of dendrite structures into globular grains, which have α-Mg phase and ß-Mg17Al12. Small spherical grain shape and spread evenly with a size of 40.08 μm obtained at temperatures of 500°C and size 77.2 μm at temperatures 540°C.